(untitled) (Biological Sciences - PJSIR, 2020)
Promoters are of great importance for controlling gene expression. There are various regulatory regions within promoters which are crucial for expression specificity. Depending upon mode of expression, promoters can be divided into constitutive, tissue/developmental stage specific or inducible promoters. For expression of certain gene, there is interplay of cis acting element located on promoter and transcription factors. Cotton fibre promoters are of great importance in biotechnology as these may be used to express fibre genes in cotton fibres specifically. Although most of cotton fibre gene promoters show expression in fibres but some of them also exhibit expression in various other organs like trichomes, pedicles and vascular tissues. Due to difficulties in somatic embryogenesis in cotton, these promoters are mostly studied in heterologous systems like Arabidopsis and tobacco. In this article, expression pattern of some cotton fibre genes promoters have been reviewed.